The Effectiveness of Using Jigsaw in Teaching Reading Comprehension across different Personality - M. Adib Efendi (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
The purposes of the study were to test assumption underlying the effect of the jigsaw in teaching reading, the sign in the achievement of an extrovert student and extrovert student, and the interaction between jigsaw and personality. Before the researcher give the treatment in experiment class the researcher give questionnaire about personality into class, the questionnaire from EPI. The place of the research at MA Sabilul Muttaqin with the students 47 of eleventh grade that consist of 25 student in experimental they are 17 extrovert students and 8 introvert student and 22 in control they are 14 extrovert students and 8 introvert student. The researcher used experimental factorial design is a procedure of testing a hypothesis by setting up a situation in which strength of the relationship between variable can be tasted. And the research used Two Way ANOVA to calculate the data. From the result is jigsaw technique more effective than conventional technique, and there are differences on significant between extrovert and extrovert. An interaction between jigsaw and personality. Keyword: Effectiveness, Jigsaw, Descriptive text, Personality